COMPARING EXTERNAL TOTAL LOAD, ACCELERATION AND DECELERATION OUTPUTS IN ELITE BASKETBALL PLAYERS ACROSS POSITIONS DURING MATCH PLAY (Kinesiology, 2018)
The aim of this study was to compare external load, calculated by an accelerometer training load model, the number and intensity of accelerations and decelerations and the acceleration:deceleration ratio between playing positions during basketball matches. Twelve elite male basketball players (mean±SD, age: 25.5±5.2 years (range: 19-36 years); 201.4±8.6 cm; body mass: 98.4±12.6 kg) were monitored during two official matches. An accelerometer training load model and the number of accelerations and decelerations were used to assess the physical demands. Magnitude-based inferences and effect sizes (ES) were used to assess possible differences between positions: Point Guards (PG), Shooting Guards (SG), Small Forwards (SF), Power Forwards (PF) and Centers (C). Elite basketball players in all positions presented higher maximal decelerations than accelerations (ES=2.70 to 6.87) whereas the number of accelerations at moderate intensities was higher than deceleration (ES=0.54 to 3.12). Furthermore, the acceleration:deceleration ratio (>3 m∙s-2) was significantly lower in players on the perimeter (PG and SG) than in PF and C (ES=1.03 to 2.21). Finally, PF had the lowest total external load (ES=0.67 to 1.18). These data allow us to have a greater knowledge of the external demands in matches and this information could be used in the planning of training programs.